Frequency of serotypes of Streptococcus pyogenes in different diseases - Mitchell, E. S. (1962)
During an 18-month period 1,002 strains of Streptococcus pyogenes, consecutively isolated in the laboratory from a wide variety of lesions, were typed by the precipitin and slide-agglutination tests. The relative frequency of serotypes in different diseases was examined and a close association between type 4 in scarlet fever and type 3.13 in impetigo noted. An apparent lack of any relationship between particular serotypes and streptococcal sore throat was evident. The difficulty of distinguishing the more virulent types of Str. pyogenes and correlating a type-specific disease relationship is discussed.